2022-RA-1598-ESGO What has greatest impact on risk of recurrence in primary epithelial ovarian cancer?. (20th October 2022) - Lischke, Emma Frederike; Wallwiener, Diethelm; Bachmann, Cornelia
Abstract : Introduction/Background: Ovarian cancer (OC) is the eighth most common cancer in women in Germany and the deadliest gynecologic malignancy. Many risk factors for OC are known (age/obesity/hereditary forms etc.). Overall 70–80% of OC patients suffer from recurrences. This gives reason to further improve the prediction of the risk of recurrent OC and the quantification of the impact of various factors on the occurrence of relapse. Methodology: This work includes 137 consecutive patients that were treated for primary epithelial OC (EOC) at our department from 2014 through 2016 and who were followed up through 1st of April 2020. Overall median follow-up time was 39 months. The patients were subdivided into 2 groups depending on the occurrence of relapse ( recurrence-, n=105; no recurrence -group, n=32). Data were retrospectively analyzed and tested for differences in relapse behavior. Results: Overall recurrence-rate was 76.6%. In the recurrence-group median progression free survival was 14 (2–56) months and median overall survival (OS) was 31 (6–68) months. In the no recurrence-group median OS was 51.5 (39–73) months. The largest impact regarding the incident of recurrence was observed for FIGO-stage III (OR 26.33, 95% CI 6.6–105.3, P<0.001) and IV (OR 28.89, 95% CI 5.0–165.6, P<0.001), followed by initial existence of peritoneal carcinomatosis (OR 9.96, 95% CI 4.0–25.0, P<0.001) and poor differentiation (G3) (OR 9.43, 95% CI 2.6–34.2, P<0.001). Recurrence was more likely for high-grade serous cancer (HGSC) in comparison to other histologies (OR 3.31, 95% CI 1.4–7.9, P= 0.007) and in case of lymph-node metastasis (OR 2.84, 95% CI 1.2–6.7, P=0.016). Conclusion: The likelihood of EOC recurrence is primarily determined by the FIGO stage. Stage III/IV increase the probability of recurrence by 26 and 29, respectively. Furthermore, recurrence is more likely for G3- and high-grade serous carcinoma, although these factors have less impact on occurrence of relapse than FIGO-stage.